Effect of Potassium Nitrate on Anti-Caking Performance of AN-based NPK Granular Compound Fertilizer. Issue 208 (12th June 2020) - Hong, Wei; Peng, Guirong; Wu, Shu; Wang, Jinming; Yang, Zhenjun; Ru, Tiejun
Abstract: Agricultural ammonium nitrate(ANP) is one of the main raw materials for the production of AN-based compound fertilizer. The IV-III phase transition of ammonium nitrate(AN) is one of the main reasons for the caking of AN-based compound fertilizer(NPK). Potassium salts used for the production of compound fertilizers are usually K2 SO4 (KS). In this paper KNO3 (KN) was added to improve the anti-caking properties of AN-based NPK. The IV-III phase transition of ANP and the effects of KN, KS, NH4 SO4 (NS), and NH4 H2 PO4 (NP) on the solid phase transitions of ANP was investigated by differential scanning calorimetry (DSC) and powder X-ray diffractometer(XRD). The results showed that the phase transformation inhibition effect of KN and KS on ANP was better than that of NS and NP. In this experiment, KN was used to replace part of KS in the formula of AN-based NPK, and the granular fertilizer with different contents of KN were prepared, the anti caking properties and hygroscopicity of the fertilizer were tested. The results showed that although the content of potassium in the compound fertilizer remained unchanged, with the increase of the content of KN and the decrease of the content of KS in the formula, the anti-caking performance and hygroscopicity of the AN-based NPK were obviously improved.